ENSO Atmospheric Teleconnections and Their Response to Greenhouse Gas Forcing. (17th February 2018) - Yeh, Sang‐Wook; Cai, Wenju; Min, Seung‐Ki; McPhaden, Michael J.; Dommenget, Dietmar; Dewitte, Boris; Collins, Matthew; Ashok, Karumuri; An, Soon‐Il; Yim, Bo‐Young; Kug, Jong‐Seong
Abstract: El Niño and Southern Oscillation (ENSO) is the most prominent year‐to‐year climate fluctuation on Earth, alternating between anomalously warm (El Niño) and cold (La Niña) sea surface temperature (SST) conditions in the tropical Pacific. ENSO exerts its impacts on remote regions of the globe through atmospheric teleconnections, affecting extreme weather events worldwide. However, these teleconnections are inherently nonlinear and sensitive to ENSO SST anomaly patterns and amplitudes. In addition, teleconnections are modulated by variability in the oceanic and atmopsheric mean state outside the tropics and by land and sea ice extent. The character of ENSO as well as the ocean mean state have changed since the 1990s, which might be due to either natural variability or anthropogenic forcing, or their combined influences. This has resulted in changes in ENSO atmospheric teleconnections in terms of precipitation and temperature in various parts of the globe. In addition, changes in ENSO teleconnection patterns have affected their predictability and the statistics of extreme events. However, the short observational record does not allow us to clearly distinguish which changes are robust and which are not. Climate models suggest that ENSO teleconnections will change because the mean atmospheric circulation will change due to anthropogenic forcing in the 21st century, which is independent of whether ENSO properties change or not. However, future ENSO teleconnection changes do not currently show strong intermodel agreement from region to region, highlighting the importance of identifying factors that affect uncertainty in future model projections. Key Points: The character of ENSO as well as the ocean mean state has changed since the 1990s, resulting in changes in ENSO atmospheric teleconnections Changes in ENSO teleconnection patterns have affected their predictability and the statistics of extreme events Climate models suggest that changes in the mean atmospheric circulation will affect ENSO teleconnections in the 21st century